Interface properties influence the effective dielectric constant of composites - Chatzigeorgiou, George; Javili, Ali; Steinmann, Paul (Philosophical Magazine, 2015)
In this work we propose a micromechanics model, based on the composite spheres assemblage method, for studying the electrostatic behaviour of particle and porous composites when the interface between the particle (or the pore) and the matrix has its own independent behaviour. Examples from experimental results in porous media and particle composites are utilized to demonstrate the models capabilities. The current model shows a better agreement with experiments compared with other available studies. Furthermore, it is shown that the interface dielectric constant is independent of the experiments which prove its nature as a material parameter.
CRIS-Team Scopus Importer:2022-08-05
Keywords: coating; electrical properties; fibre/matrix bond; interface; nanocomposites